Effects of exercise on the sleep microarchitecture in the aging brain: A study on a sedentary sample - Cassim, Tuan Z.; McGregor, Keith M.; Nocera, Joe R.; García, Violet V.; Sinon, Christopher G.; Kreuzer, Matthias; García, Paul S. (Frontiers in Systems Neuroscience, 2022)
Having a healthy sleep pattern plays a vital role in one’s overall health. Sleep in the elderly is characterized by decreased slow-wave sleep and an increase of REM sleep. Furthermore, quantitative electroencephalographic (qEEG) studies have shown an age-related attenuation of total EEG power in sleep. However, exercise has been shown to improve sleep across all age groups. In this study, we used the Sleep Profiler™ EEG Sleep Monitor to observe EEG changes occurring during sleep following an aerobic exercise intervention. This study was done on older adults (N = 18, with only five subjects containing both pre- and post-data of sufficient quality for analysis) with an age range 60–85 years. The aerobics regimen was performed three times weekly for 12-weeks commencing with 20-min sessions. The time of each session progressed by 1–2 min/session as needed to a maximum time of 45 min per session. The macro-architecture (sleep stages) and microarchitecture (EEG) results were analyzed using MATLAB. For the microarchitecture, our results showed more deep sleep following the aerobic exercise regimen. Furthermore, for the microarchitecture, out results shows an increase in total EEG power post-exercise in both light (N1 and L1) and deep sleep (N2 and N3). These preliminary changes in sleep the microarchitecture suggest that non-pharmacologic methods might mitigate age-related EEG changes with potential implications for neurocognitive health.